NETopathic Inflammation in Chronic Obstructive Pulmonary Disease and Severe Asthma - Uddin, Mohib; Watz, Henrik; Malmgren, Anna; Pedersen, Frauke (Frontiers in Immunology, 2019)
Neutrophils play a central role in innate immunity, inflammation and resolution. Unresolving neutrophilia features as a disrupted inflammatory process in the airways of patients with chronic obstructive pulmonary disease (COPD) and severe asthma. The extent to which this may be linked to disease pathobiology remain obscure and could be attributable to confounding by indication of glucocorticoids or concomitant respiratory infections. The formation of neutrophil extracellular traps (NETs) represents a specialised host defence mechanism that entrap and eliminate invading microbes. NETs are web-like scaffolds of extracellular DNA in complex with histones and neutrophil granular proteins, such as myeloperoxidase and neutrophil elastase. Distinct from apoptosis, NET formation is an active form of cell death that could be triggered by various microbial, inflammatory and endogenous or exogenous stimuli. NETs are reportedly enriched in neutrophil-dominant refractory lung diseases, such as COPD and severe asthma. Evidence for a pathogenic role for respiratory viruses (e.g. Rhinovirus), bacteria (e.g. Staphylococcus aureus) and fungi (e.g. Aspergillus fumigatus) in NET induction is emerging. Dysregulation of this process may exert localised NET burden and contribute to NETopathic lung inflammation. Disentangling the role of NETs in human health and disease offer unique opportunities for therapeutic modulation. NET-stabilising agents such as CXCR2 antagonists are being investigated in proof-of-concept studies in patients with COPD to provide mechanistic insights. Clinical validation of this type could lead to novel therapeutics for multiple CXCR2-related NETopathologies. In this Review, we discuss the emerging role of NETs in the clinicopathobiology of COPD and severe asthma and provide an outlook on how novel NET-stabilising therapies could be leveraged to immunostabilise NETopathic inflammation in disease-specific phenotypes.